PROGRESSIVE ART EDUCATION: A STEP-BY-STEP APPROACH FOR SECONDARY SCHOOL STUDENTS - Boboqulov Javohir Hamzayevich (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores the progressive development of art education for secondary school students through a step-by-step pedagogical approach. The study emphasizes that systematic and gradual instruction in art not only enhances students’ technical drawing and painting skills but also fosters their creative imagination, aesthetic awareness, and critical thinking abilities. The step-by-step method provides a structured framework that aligns with students’ psychological and developmental stages, enabling them to progress from basic visual exercises to more complex creative compositions. Incorporating innovative pedagogical strategies such as interactive learning, project-based art practice, and digital visualization enhances engagement and allows students to express themselves more freely. The article concludes that a progressive, stage-based approach in art education promotes artistic literacy, independent creativity, and deeper understanding of visual culture among middle school learners.